2020
DOI: 10.30906/1026-2296-2020-27-1-26-32
|View full text |Cite
|
Sign up to set email alerts
|

Detection Probability and Site Occupancy of the Granular Spiny Frog (<i>Quasipaa verrucospinosa</i>) in the Tropical Rain Forests of Bach Ma National Park, Central Vietnam

Abstract: Amphibian species are rarely detected with perfect accuracy, regardless of the method employed. A large-scale assessment for Quasipaa verrucospinosa occupancy was conducted at 35 sites in the primary forest and 42 sites in the secondary forest of Bach Ma National Park, central Vietnam. Based on the detection data for each site, the distribution of Q. verrucospinosa was estimated in different habitat types using occupancy models. From the best model among all performed models, we estimated a site occupancy prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…The samples of this species used in our study were captured during postbreeding season to reduce energetic cost; the dimorphic limb muscles that are androgen dependent might regress when animals are non‐reproductive (Monks & Holmes, 2018). Ngo et al (2012) have reported that the gonadal volumes of males and females of H. guentheri vary significantly among seasons based on specimens from Bach Ma National Park of Central Vietnam. Specifically, the ovaries of adult females have largest volumes (7.14 cm 3 ) between March and August and small volumes (3.09 cm 3 ) from September to February, whereas the testicular volumes of mature males dramatically increase from April to July and fall from September to January.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples of this species used in our study were captured during postbreeding season to reduce energetic cost; the dimorphic limb muscles that are androgen dependent might regress when animals are non‐reproductive (Monks & Holmes, 2018). Ngo et al (2012) have reported that the gonadal volumes of males and females of H. guentheri vary significantly among seasons based on specimens from Bach Ma National Park of Central Vietnam. Specifically, the ovaries of adult females have largest volumes (7.14 cm 3 ) between March and August and small volumes (3.09 cm 3 ) from September to February, whereas the testicular volumes of mature males dramatically increase from April to July and fall from September to January.…”
Section: Discussionmentioning
confidence: 99%
“…During amplexus, males use their forelimbs to clasp the females around the chest for hours or even for days until oviposition occurs (Zou et al, 2003). Previous studies mainly focus on its mating behaviour (Zou et al, 2003), age structure (Li et al, 2010), testis size asymmetry (Liu et al, 2011), ovarian and testis volume change with months (Ngo et al, 2012), brain size variation among populations (Gu et al, 2017), and acoustic communication (Jia et al, 2019). However, little information is known about the sexual dimorphism in limb muscle mass of H. guentheri during non-breeding season.…”
mentioning
confidence: 99%
“…En base a ello y al interés puntual (objetivos planteados en este capítulo) de determinar qué factores ambientales afectan la ocupación de las especies objetivo, se calculó el modelo estándar de ocupación (con menor número de parámetros) priorizando la incorporación del mayor número de variables de detección y de ocupación posibles. Estos modelos son utilizados actualmente para identificar la respuesta especie-específica de los anfibios en diferentes sitios con características particulares (Swartz et al, 2020;Ngo et al, 2020). La función para el cálculo de estos modelos de ocupación consta de dos partes, la probabilidad de detección (p) y la predicción de ocupación (Psi ψ) (Kéry y Royle, 2016).…”
Section: Construcción De Modelosunclassified
“…Analizados los modelos, observamos que un porcentaje importante de las especies no son detectadas en los relevamientos de campo debido a diversos factores como, las precipitaciones, la hora del día y el momento del año. Esta dificultad concuerda con muchas de las observaciones realizadas por otros autores (Heard et al, 2006;Canessa et al, 2012;Ngo et al, 2020) quienes señalaron la influencia de la época del año, la hora del día y el clima en la detectabilidad de especies anfibios en otras partes del mundo. Además de ello, consideramos que otros factores, como los comportamentales (la potencia y frecuencia de canto, especies crípticas, entre otros) podrían explicar las diferencias de detección entre las especies (Mackenzie et al, 2002;Benedikt y Pellet, 2009).…”
Section: Semiárido Y Las Variables Ambientales: Variables De Sitio (Ocupación) Y Variables De Muestra (Detección)unclassified